Association of kidney donor risk index with the outcome after kidney transplantation in the Eurotransplant Senior Program - Schamberger, Beate; Lohmann, Dario; Sollinger, Daniel; Stein, Raimund (Annals of transplantation, 2018)
Background: We evaluated the Kidney Donor Risk Index (KDRI) scoring system for kidney transplantation in the Eurotransplant Senior Program (ESP) that allocates kidneys from older donors to older recipients (³65 years). Material/Methods: We retrospectively analyzed data of 37 kidney transplant recipients and 36 kidney donors who participated in kidney transplantation program according to the ESP at our center from January 2004 until December 2013. Results: Mean recipient and donor age was 67.9±2.6 and 70.5±4.0 years respectively. The mean KDRI score was 1.7±0.27. Uncensored graft survival after 1 year and 5 years was 64.2% and 53.7% respectively. Subgroup analysis showed that in kidney transplantation with KDRI >1.83, graft survival was significantly reduced compared to lower KDRI subgroups. KDRI was significantly correlated with serum creatinine level at discharge (r=0.4). Conclusions: ESP kidneys represent a group of high-risk grafts with high KDRI scores. Higher KDRI scores in ESP kidneys was associated with reduced postoperative short-term and long-term graft outcomes. KDRI might be useful in decision-making for selecting donors for ESP kidney transplantation.